The Population Health Value Framework: Creating Value by Reducing Costs of Care for Patient Subpopulations With Chronic Conditions. (September 2019) - Gupta, Reshma; Roh, Lily; Lee, Connie; Reuben, David; Naeim, Arash; Wilson, James; Skootsky, Samuel A.
Abstract : Problem: With the growth in risk-based and accountable care organization contracts, creating value by redesigning care to reduce costs and improve outcomes and the patient experience has become an urgent priority for health care systems. Approach: In 2016, UCLA (University of California, Los Angeles) Health implemented a system-wide population health approach to identify patient populations with high expenses and promote proactive, value-based care. The authors created the Patient Health Value framework to guide value creation: (1) identify patient populations with high expenses and reasons for spending, (2) create design teams to understand the patient story, (3) create custom analytics and spending-based risk stratification, and (4) develop care pathways based on spending risk tiers. Primary care patients with three chronic conditions—dementia, chronic kidney disease (CKD), and cancer—were identified as high-cost subpopulations. Outcomes: For each patient subpopulation, a multispecialty, multidisciplinary design team identified reasons for spending and created care pathways to meet patient needs according to spending risk. Larger, lower-risk cohorts received necessary but less intensive interventions, while smaller, higher-risk cohorts received more intensive interventions. Preliminary analyses showed a 1% monthly decrease in inpatient bed day utilization among dementia patients (incident rate ratio [IRR] 0.99, P < .03) and a 2% monthly decrease in hospitalizations (IRR 0.98, P < .001) among CKD patients. Next Steps: Use of the Patient Health Value framework is expanding across other high-cost subpopulations with chronic conditions. UCLA Health is using the framework to organize care across specialties, build capacity, and grow a culture for value.